Pengaruh Pemberian Kurma Untuk Meningkatkan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia di Desa Bumisari Natar - Ramadhiena Destia Murtisari; Devi Kurniasari; Anissa Ermasari; Nurul Isnaini (Inovasi Kesehatan Global, 2025)
Anemia in pregnant women is a health problem that is often faced in Indonesia. Anemia requires special attention because it can have a significant impact on maternal and neonatal health. Based on data for May 2024 at the Bumisari Village posyandu, there were 67 pregnant women and 46.2% of them had anemia. An effort to increase hemoglobin levels in pregnant women with anemia is by giving them dates which contain high levels of iron. The aim of the research is to determine the effect of giving dates to increase hemoglobin levels in pregnant women with anemia in Bumisari Natar Village in 2024. Quantitative research type, pre-experimental research method with a one group pretest-posttest design approach. The population is all 67 pregnant women recorded in May 2024 with a sample of 31 respondents. 7 dates were given per day for 7 consecutive days. Data collection used observation sheets, univariate and bivariate data analysis (t-test). Based on the research results, it is known that the average hemoglobin level of pregnant women with anemia before consuming dates is 9,652 gr/dl, while the average hemoglobin level of pregnant women with anemia after consuming dates is 11,545 gr/dl. There was an effect of giving dates to increase hemoglobin levels in pregnant women with anemia in Bumisari Natar Village in 2024 (p-value 0.001) with a difference in increase in hemoglobin levels of 1,893 gr/dl. Advice for health workers, especially midwives, is to advise pregnant women to consume dates as a companion to Fe tablets because they can increase hemoglobin levels in pregnant women.